PRODUCTION PROCESS WASTE ANALYSIS WITH LEAN MANUFACTURING APPROACH IN COPPER CRAFTS INDUSTRY - Darsini darsini (Journal of Industrial Engineering and Halal Industries, 2021)
Competition in the industrial world is increasingly making manufacturing companies to continue to improve continuously the quality, price, quantity of production and timely delivery of their products to provide satisfaction to consumers/customers. In the research analyzed, namely the waste that occurs in the copper craft industry UD. Setya Budhi, and this study aims to analyze waste and what are the factors causing it. This study uses a Lean Manufacturing approach with data processing using the Value Stream Mapping (VSM) and Failure Mode And Effect Analysis (FMEA) methods. The data needed for this research starts from observations of the work environment, facility layout, production flow and production time. As well as the stages of interviews and questionnaires to complete the required data. From the analysis using the Value Stream Mapping (VSM) method, the results obtained are 71.60% value added, 7.39% non value added, and necessary but non value added 21.01%, then the analysis uses the Failure Mode And Effect method. Analysis (FMEA) obtained the highest RPN value from Waste Defect of 252 points, Waste Waiting 590 points, Waste Transportation 600 points, and Waste Motion 700 points, which means that there is still waste that occurs in the company. So it is necessary to have a significant evaluation of the layout of the facility or production layout and the provision of SOP classification in each department.